"I wish my parents had…": How willing are Asian American TRAs to discuss race with their White parents? - Nardone Mahoney, Marisa. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Child Development.; Advisor: Ellen Pinderhughes.; Committee: Sara Johnson, Annabelle Atkin, and Adam Kim.; Keywords: Developmental psychology, and Asian American studies.